Proceedings of the Twenty-first Annuals conference of the Association of Muslim Social Scientists East Lansing, Michigan, Oktober 30 November, 1992 - ASSOCIATION... (The International Institute of Islamic Thought, 1993)
oen, c.1-7/wk, c.8-9/stc13,c.10